Analisis terhadap Peranan Polri Sebagai Penyidik Dalam Tindak Pidana Penebangan Hutan Tanpa Izin (Penelitian Berkas Perkara Nomor BP/83/XI/2010/RESKRIM pada Polres Tulang Bawang) - Satrio Nur Hadi; Tahura Malagano (Universitas Batanghari Jambi, 2020)
Forest development is a national development target that is expected to provide maximum benefits for the people's welfare, in fact this is now very difficult to happen, because there are many cases of logging without permission from the authorized official. This is the case in the Sungai Buaya Register 45 Forest Area, Mesuji Regency, Lampung. In the case file Number BP / 83 / XI / 2010 RESKRIM to the Tulang Bawang Pokes that the suspect named Komang Salie alias Komang Bon alias Wayan Putra bin Wayan Mije, is suspected of having committed a criminal act of logging without the permission of the authorized official, in a case which is suspected by everyone. prohibited from occupying and or working and or using, encroaching, cutting trees and harvesting or collecting forest products without having the right and permission from the authorized official and carrying tools specifically used to cut, cut or cut trees in the forest area without a permit authorized officials, and those who commit, who order to do, participate in the act or those who deliberately provide assistance at the time the crime is committed or those who deliberately provide opportunities, means to commit the crime, as referred to in Article 50 paragraph (3) letters a, b, e, and k Jo Article 78 paragraph (2), (5), and ( 10) Law Number 19 of 2004 concerning Amendments to Law Number 41 of 1999 concerning Forestry, Jo Articles 55, 56 of the Criminal Code. The problem in this research is what is the role of the National Police as an investigator in the criminal act of logging without the permission of the authorized official and what factors are the factors that hinder the role of the Police as an investigator in the criminal act of logging without the permission of the authorized official. The method that the author uses in this research is to use normative and empirical approaches, primary and secondary data types, data collection methods with literature study and field studies, and descriptive qualitative data analysis. Based on the results of the research, the role of the National Police as an investigator in the crime of forest logging without the permission of the authorized official case number BP / 83 / XI / 2010 / RESKRIM at the Tulang Bawang Police, among others, before the investigation was carried out, an investigation was first carried out to determine the truth of the criminal act that occur. The investigation is based on KUHAP and Law Number 02 of 2002 concerning the Police.